COVID-19 Impact and Tourism Recovery Geopolitics: A Paradox in Tanzania - Lema, Godwin (Tanzania Journal for Population studies and Development, 2021)
Responses to recover from the first wave of COVID-19 crisis created a divide globally partly as some countries interpreted the pandemic defiantly, aptly to rescue their tourism, among other sectors. A lasting tragedy of the pandemic impact continues to particularly frustrate global tourism mobility unless strategic consensus is found. The strategy that Tanzania adopted to restore tourism early amidst the pandemic is examined in this article. It draws from headlines, surveys, tourist arrival statistics and interviews with industry actors. Findings revealed that from 16th March 2020, Tanzania reported coronavirus infections and few associated COVID-19 deaths for nearly three months after the pandemic outbreak. Airspace and border closures from 20th March halted tourist arrivals resulting to business closures, unemployment and severe revenue loss. Reopening of international gateways from May 2020, through adopting standard operating procedures, reverted a sharp decline of arrivals experienced in April-May to a gradual increase of arrivals from June onwards. Despite the early reopening, the number of international tourist arrivals were far below the pre-crisis levels, implying that the country’s efforts were hardly resolving the tourism post-pandemic recovery paradox. Consensus is vital in restarting and sustaining post-pandemic tourism. This article contributes to the geopolitics of COVID-19, tourism recovery and resilience in Tanzania and globally, calling for continued collaboration among national and international tourism actors to chart out a post-pandemic sustainable tourism recovery strategy, as a policy response.